The role of echocardiographic screening in reducing the burden of rheumatic heart disease in Latin America - Manuel Urina-Jassir; Maria Alejandra Jaimes-Reyes; Daniela Urina-Jassir; Manuel Urina-Triana; Miguel Urina-Triana (Pan American Health Organization, 2023)
The objectives of this article are to reflect on the rationale behind the use of echocardiographic screening for rheumatic heart disease and to provide key recommendations about steps needed to implement and improve echocardiographic screening programs in Latin America. Rheumatic heart disease remains a public health problem affecting mainly low-income and lower-middle-income countries and populations. Latin America is an area with economic inequalities, and the epidemiology of rheumatic heart disease remains largely unknown. Echocardiographic screening is useful for updating the epidemiology and providing early diagnosis of the disease. We discuss different approaches used in successful echocardiographic screening programs worldwide and in Latin America. We then identify the key elements needed to establish successful echocardiographic screening programs in Latin America, including increased awareness and involvement from multiple sectors (e.g. the community, health care professionals, scientific organizations and public health entities), identification of areas in need, development of a plan and structure that include different screening approaches, and how to ensure appropriate follow up for those who screen positive.